Aplikasi Pupuk Hayati Fosfat dan Amelioran Organik untuk Meningkatkan C-Organik, Pertumbuhan dan Hasil Tanaman Jagung (Zea mays L) pada Tanah Masam - Fiqriah Hanum Khumairah; Anggi Jingga; Betty Natalie Fitriatin; Tualar Simarmata (Soilrens, 2022)
Acidity is still a serious obstacle for maize cultivation due to the very low availability of phosphorus. The use of phosphate biofertilizers, containing phosphate solubilizing bacteria as an active ingredient, together with organic ameliorants was expected to be able to provide phosphorus for plants, increase the organic C content in the soil. Experiment aimed to find the proper application of phosphate biofertilizers along with organic ameliorants to support the growth and yield of maize on acid soils. The experiment used a factorial randomized block design with phosphate biofertilizers and organic ameliorants as the first factor and doses of P fertilizer as the second factor, which was repeated three times. Results showed that the application of phosphate bifertilizers consisted of Enterobacter ludwigii + Bulkholderia vietnamiensis + Citrobacter amalonaticus were applied together with organic ameliorants with the composition of chicken manure compost (25%): municipal waste compost (25%): coconut shell biochar (50%) at a dose of 5 tons/ha was able to increase plant dry weight and dry weight of shells per hectare by 248.87 g and 12.960 kg. The C-organic content of the soil had no significant effect due to the application of phosphate biofertilizers and organic ameliorants. The application of phosphate biofertilizers and organic ameliorants can support the growth and yield of corn plants on acid soils.